Open Labor Markets and Firms' Substitution between Training Apprentices and Hiring Workers - Manuel Aepli; Andreas Kuhn (Institute of Labor Economics (IZA), 2019)
In this paper, we study whether Swiss employers substitute between training apprentices and hiring cross-border workers. Because both training apprentices and hiring skilled workers are costly for firms, we hypothesize that (easier) access to cross-border workers will lead some employers to substitute away from training their own workers. We account for potential endogeneity issues by instrumenting a firm's share of cross-border workers using a firm's distance to the national border and therefore its possibility to fall back on cross-border workers to satisfy its labor demand. We find that both OLS and 2SLS estimates are negative across a wide range of alternative specifications, suggesting that firms substitute between training and hiring workers when the supply of skilled workers is higher. Our preferred 2SLS estimate implies that the increase in firms' share of crossborder workers within our observation period, from 1995 to 2008, led to about 3,500 fewer apprenticeship positions (equal to about 2% of the total number of apprentice positions).
Keywords: D22; J23; J61; M53; 330; immigration; cross-border workers; firm behaviour; labor demand; substitution effects; apprenticeship training